Sustainable Strategies and Practical Research in Innovative Structural Packaging Design - Alexandra Ștefana Ghioc (Journal of Research and Innovation for Sustainable Society)
This paper aims to examine the paradigm shifts that structural packaging design is currently facing in terms of sustainability exposing the key changes that address not only consumer’s behaviour, but also the manufacturing process from early stages of the design with radical approaches to incremental solutions, that are contributing on a large-scale ecological transformation. The paper presents 4 case studies as practical innovative research resulted from complex design processes and methodologies analysis displaying viable solutions in various packaging sectors such as cosmetics, food, and beverages.